Evaluation of ovarian reserve parameters in patients who underwent detorsion because of ovarian torsion - Konal, Merve; Köroğlu, Nadiye; Aslan Çetin, Berna; Yıldırım, Gonca; Yıldırım, Gökhan (My University, 2024)
Objectives: Ovarian torsion is a gynecologic emergency that can cause loss of ovarian function. The aim of the study was to evaluate the ovarian reserve of the patients who were operated for detorsion because of ovarian torsion. Materials and Methods: The medical records of the patients who underwent detorsion for ovarian torsion in our clinic between January 2013 and June 2017 were investigated. Ovarian reserve parameters including ovarian volume, antral follicle count and ovarian artery resistance index (RI) were evaluated by ultrasonography in post-operational period. Patients that had oophorectomy due to torsion or who had another ovarian surgery before or after torsion and pregnant women were not included in the study. The ovarian volume, antral follicle count and ovarian artery RI in the operated side were compared with the contralateral ovary. Results: Thirty-four women meeting the inclusion criteria were examined by ultrasonography in the early follicular phase of their cycles. Antral follicle count, ovarian volume and ovarian artery RI were decreased significantly (p<0.001, p<0.001 and p<0.001, respectively) in the operated ovary compared to the contralateral ovary. Sixteen patients who were treated by detorsion, underwent cystectomy at the same time. No significant difference was observed in ovarian reserve of the patients who had cystectomy together with detorsion compared to those who were operated only with detorsion. Conclusion: Antral follicle count, ovarian volume and ovarian artery RI were significantly decreased after detorsion operation in the operated side compared to the contralateral ovary.
Keywords: Antral Follicle Count; Detorsion; Ovarian Reserve; Ovarian Torsion; Ovarian Volume